Saúde mental e o campo sociojurídico: o "estado da arte do debate" com a reforma psiquiátrica - Mathes, Priscilla Gomes (2012)
In the present paper we aim to outline the trajectory of the theme of mental health in the social-judicial field, in an attempt to visualize the "state of the art of debate" of the academic production on this theme in the last decade (2001-2011), in the knowledge production areas of the applied human and social sciences (CAPES, 2009). This problem emerges as a relevant issue to be object of research due to changes that have occurred in several mental health spaces after the psychiatric reform movement that took place in Brazil. This paper has an innovative character, in view of the originality of the construction of the "state of the art" on the issue of mental health. Therefore, it has an eminently exploratory character. In order to achieve the proposed objectives, a database was constructed as a tool for analyzing the universe of works that were found about the theme of mental health in the social-judicial field in the main means of publication with virtual access. However, it was identified that, despite the advances perceived in the public policies in the area of mental health in this country, the scientific-technical production does not seem to have accompanied these changes with the same intensity.No presente trabalho, pretende-se traçar uma trajetória do tema da saúde mental no campo sociojudiciário, com o objetivo de tentar visualizar o "estado da arte do debate" da produção acadêmica dessa temática na última década (2001-2011) nas áreas de produção de conhecimento das ciências humanas e sociais aplicadas (CAPES, 2009). Essa problemática aparece como uma questão relevante para ser objeto de pesquisa em decorrência de mudanças ocorridas em diversos espaços da saúde mental a partir do movimento de reforma psiquiátrica ocorrido no Brasil. Este trabalho apresenta um caráter inovador, considerando o ineditismo da construção do "estado da arte" sobre a temática da saúde mental, sendo assim, de caráter eminentemente exploratório. Visando alcançar os objetivos propostos, realizou-se a construção de uma base de dados como instrumento para observar o universo de trabalhos encontrados em torno da temática da saúde mental no campo sociojudiciário, nos principais meios de publicação com acesso virtual. Identificou-se, contudo, que, apesar dos avanços percebidos nas políticas públicas da área da saúde mental neste país, a produção científico-técnica não parece ter acompanhado essas modificações com a mesma intensidade